1999
DOI: 10.1037/0022-006x.67.6.945
|View full text |Cite
|
Sign up to set email alerts
|

Psychological sequelae of hate-crime victimization among lesbian, gay, and bisexual adults.

Abstract: Questionnaire data about criminal victimization experiences were collected from 2,259 Sacramento-area lesbians, gay men, and bisexuals (N = 1,170 women, 1,089 men). Approximately 1/5 of the women and 1/4 of the men had experienced victimization because of their adult sexual orientation. Hate crimes were less likely than nonbias crimes to have been reported to police. Compared with other recent crime victims, lesbian and gay hate-crime survivors manifested significantly more symptoms of depression, anger, anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
530
4
18

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 647 publications
(600 citation statements)
references
References 19 publications
40
530
4
18
Order By: Relevance
“…Also, many survey studies tend to treat sexual minority status groups collectively as a single group whilst academic research often, but not routinely (Price, 2011), considers differences between their victimisation experiences (Balsam et al, 2005;Conron, Mimiaga & Landers, 2010;Herek, 2009;Poteat, Aragon, Espelage & Koenig, 2009;Roberts et al, 2010;Warner et al, 2004). Despite their methodological differences, much of this mainly North American peer reviewed research broadly confirms the findings of survey studies conducted in the United Kingdom, and shows that lesbian, gay, bisexual and transgender individuals are at increased risk of victimisation from a range of crimes (Balsam et al, 2005;Cramer et al, 2012;D'Augelli, 1992;Herek, 1989;Herek et al, 2002;Herek, Gillis & Cogan, 1999;Kohn, 2001;Lombardi, Wilchins, Priesing & Malouf, 2001;Roberts et al, 2010;Rubenstein, 2004;Strom, 2001). In the United Kingdom, a recent small-scale study of victimisation and fear of crime in gay and heterosexual men in Manchester (Laing & Davies, 2011) found that gay men were more likely to have suffered some form of direct criminal victimisation than were heterosexual men at some point in their life (51% versus 40% respectively).…”
Section: Introductionsupporting
confidence: 63%
“…Also, many survey studies tend to treat sexual minority status groups collectively as a single group whilst academic research often, but not routinely (Price, 2011), considers differences between their victimisation experiences (Balsam et al, 2005;Conron, Mimiaga & Landers, 2010;Herek, 2009;Poteat, Aragon, Espelage & Koenig, 2009;Roberts et al, 2010;Warner et al, 2004). Despite their methodological differences, much of this mainly North American peer reviewed research broadly confirms the findings of survey studies conducted in the United Kingdom, and shows that lesbian, gay, bisexual and transgender individuals are at increased risk of victimisation from a range of crimes (Balsam et al, 2005;Cramer et al, 2012;D'Augelli, 1992;Herek, 1989;Herek et al, 2002;Herek, Gillis & Cogan, 1999;Kohn, 2001;Lombardi, Wilchins, Priesing & Malouf, 2001;Roberts et al, 2010;Rubenstein, 2004;Strom, 2001). In the United Kingdom, a recent small-scale study of victimisation and fear of crime in gay and heterosexual men in Manchester (Laing & Davies, 2011) found that gay men were more likely to have suffered some form of direct criminal victimisation than were heterosexual men at some point in their life (51% versus 40% respectively).…”
Section: Introductionsupporting
confidence: 63%
“…Third, the MIDUS screened for a limited number of psychiatric disorders and did not measure some where there might also be as-yet undetected but important differences associated with sexual orientation. In particular, given the research evidence suggesting common experiences with antihomosexual harassment and threat of violence in this population (Herek et al, 1999;, we anticipate that the prevalence of posttraumatic stress disorder might be elevated. The restricted number of disorders assessed in the survey most likely biased downward our estimates of both screening positive for any disorder or comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, homosexuality is still widely stigmatized despite greater acceptance evident in recent opinion polls of the American population (Butler, 2001). Lesbians and gay men commonly report positive histories of victimization and discrimination (Herek, Gillis, & Cogan, 1999;Hershberger & D'Augelli, 1995;Krieger & Sidney, 1997), particularly in adolescence or young adulthood (D'Augelli, Hershberger, & Pilkington, 1998;Lock & Steiner, 1999). As a consequence, homosexuality may be a risk indicator for higher rates of psychological distress and some mental disorders.…”
mentioning
confidence: 99%
“…A few risk factors have been empirically tested and significantly associated with smoking outcomes, such as internalized homophobia (Amadio & Chung, 2004), alcohol abuse and depression (McKirnan, Tolou-Shams, Turner, Dyslin, & Hope, 2006), issues involving disclosure of sexual minority status (Rosario, Schrimshaw, & Hunter, 2009), and early sexual experience (Lombardi, Silvestre, Janosky, Fisher, & Rinaldo, 2008). Socially based stressors, such as discrimination and violence victimization, are also identified risk factors salient to negative health outcomes among sexual minority men and women (Herek, Gillis, & Cogan, 1999;Mays & Cochran, 2001;Meyer, 1995).…”
Section: Introductionmentioning
confidence: 99%